Reproduction of contagious caprine pleuropneumonia reveals the ability of convalescent sera to reduce hydrogen peroxide production in vitro - Liljander, Anne M.; Sacchini, F.; Stoffel, M.H.; Schieck, Elise G.; Stokar-Regenscheit, N.; Labroussaa, F.; Heller, M.; Salt, Jeremy; Frey, J.; Falquet, L.; Goovaerts, D.; Jores, Joerg (Springer, 2019)
Contagious caprine pleuropneumonia (CCPP), caused by Mycoplasma capricolum subsp. capripneumoniae is a severe disease widespread in Africa and Asia. Limited knowledge is available on the pathogenesis of this organism, mainly due to the lack of a robust in vivo challenge model and the means to do site-directed mutagenesis. This work describes the establishment of a novel caprine challenge model for CCPP that resulted in 100% morbidity using a combination of repeated intranasal spray infection followed by a single transtracheal infection employing the recent Kenyan outbreak strain ILRI181. Diseased animals displayed CCPP-related pathology and the bacteria could subsequently be isolated from pleural exudates and lung tissues in concentrations of up to 109 bacteria per mL as well as in the trachea using immunohistochemistry. Reannotation of the genome sequence of ILRI181 and F38T revealed the existence of genes encoding the complete glycerol uptake and metabolic pathways involved in hydrogen peroxide (H2O2) production in the phylogenetically related pathogen M. mycoides subsp. mycoides. Furthermore, the expression of L-α-glycerophosphate oxidase (GlpO) in vivo was confirmed. In addition, the function of the glycerol metabolism was verified by measurement of production of H2O2 in medium containing physiological serum concentrations of glycerol. Peroxide production could be inhibited with serum from convalescent animals. These results will pave the way for a better understanding of host–pathogen interactions during CCPP and subsequent vaccine development.